Electronic and structural properties of the interface between c-Si (111) and diamond like carbon - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 1997)
The chemical and electronic structure of the interface between crystalline silicon- and diamond-like amorphous hydrogenated carbon (a-C:H) are investigated. Employing in situ photoelectron spectroscopy the formation of the interface between both materials is observed step by step in terms of chemical composition as well as in terms of band bending and band offset evolution. When the heterostructure is completed a stoichiometric SiC interface layer with a thickness of 18 Å has formed whose valence band maximum lies 0.28 eV below that of the silicon substrate and 0.4 eV above that of the a-C:H overlayer. © 1997 Elsevier Science S.A.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.IAP.exphys.electr_6
Keywords: Band bending; Band offset; c-Si:a-C:H interface; Photoelectron spectroscopy